2012
DOI: 10.5194/acp-12-8323-2012
|View full text |Cite
|
Sign up to set email alerts
|

On the observed response of ozone to NO<sub>x</sub> and VOC reactivity reductions in San Joaquin Valley California 1995–present

Abstract: Abstract. We describe the effects of nitrogen oxide (NO x ) and organic reactivity reductions on the frequency of high ozone days in California's San Joaquin Valley. We use sixteen years of observations of ozone, nitrogen oxides, and temperature at sites upwind, within, and downwind of three cities to assess the probability of exceeding the California 8-h average ozone standard of 70.4 ppb at each location. The comprehensive data records in the region and the steep decreases in emissions over the last decade a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
215
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(228 citation statements)
references
References 60 publications
12
215
0
1
Order By: Relevance
“…We note that it has been previously speculated that a missing source of VOCR is important when O 3 is high in the SJV (Steiner et al, 2008;Hu et al, 2012;Pusede and Cohen, 2012). Organic sources with this temperature dependence include molecules with emission rates controlled by their vapor pressures, biogenic VOCs from forests The temperature-dependent VOCR is equal to the measured OH reactivity minus the temperature-independent i VOCR i and minus the OH reactivities of NO 2 , NO, HONO, HNO 3 , NH 3 , and SO 2 .…”
Section: Organic Reactivity and Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…We note that it has been previously speculated that a missing source of VOCR is important when O 3 is high in the SJV (Steiner et al, 2008;Hu et al, 2012;Pusede and Cohen, 2012). Organic sources with this temperature dependence include molecules with emission rates controlled by their vapor pressures, biogenic VOCs from forests The temperature-dependent VOCR is equal to the measured OH reactivity minus the temperature-independent i VOCR i and minus the OH reactivities of NO 2 , NO, HONO, HNO 3 , NH 3 , and SO 2 .…”
Section: Organic Reactivity and Temperaturementioning
confidence: 99%
“…Skies were mostly cloudless during CalNex-SJV with the measured daily average photosynthetically active radiation (PAR) independent of temperature at daily maximum temperatures greater than 22 • C. Throughout this manuscript we define low, moderate, and high temperature regimes as follows: low -daily maximum temperatures of 17-27 • C (days between 1 May-31 October), moderate -daily maximum temperatures of 28-33 • C, and high -daily maximum temperatures of 34-45 • C. In 2010 there were 38 low temperature days, 54 moderate temperature days, and 80 high temperature days. These temperature cutoffs were selected in order to be consistent with Pusede and Cohen (2012). We also refer to the 2010 average low, moderate, and high temperatures, 24.7 • C, 30.8 • C, and 36.4 • C, which are averages of the 2010 1 h daily maximum temperature record and not of the 1 h daily maximum temperatures observed during the cooler, springtime CalNex-SJV study period.…”
Section: Calnex-sjv Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This NO x sensitivity translates to regional environmental impacts. For example, the high-NO x oxidation of isoprene controls the production of tropospheric ozone in regions rich with biogenic hydrocarbons [1][2][3] by accelerating the cycling of NO x and producing NO x reservoir species (e.g., organic nitrates and peroxynitrates). Isoprene chemistry also affects global climate primarily through the formation of secondary organic aerosol (SOA).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, reductions in O 3 precursor emissions in economically developed countries have resulted in decreases in tropospheric O 3 levels (Schultz and Rast, 2007;Butler et al, 2012;Pusede et al, 2012); however, in some regions, increases in O 3 have also been reported. For instance, from an analysis of O 3 data from 179 urban sites over France during 1999, Sicard et al (2016 reported an increasing trend in the annual averages of 0.14 ± 0.19 ppb yr −1 , and in the medians of 0.13 ± 0.22 ppb yr −1 , attributed to long-range transport and reduced O 3 titration by NO due to reductions in local NO x emissions.…”
Section: Introductionmentioning
confidence: 99%